Cambios en la producción y consumo de viandas en Cuba - Norma Helen Juárez (Revue d'ethnoécologie)
The food culture of a society is the way in which social groups have historically classified, valued and prepared their food. It is not static but is constantly changing. This paper aims to illustrate how the global socio-political changes at different levels have effects that disrupt daily life, including the taste for new foods and hence change culinary traditions. To illustrate this thesis, we focus on a case study done in Cuba, a country that since the middle of the last century, has faced major political and social upheavals. The study is of the village of Güira de Melena, located in the province of Artemisa. The focus of analysis was the use of "viandas", a term constituting a food group composed of various roots, tubers, rhizomes, banana and squash of the genuses Maníhot, discorea, Xanthosoma, ipomoea, solanum, colocasia, musa y cucúrbita. Except for the potato (Solanum tuberosum Sw), the different varieties of viandas, are well adapted to the climatic conditions of the country, all of which are considered essential products both gastronomically and with respect to the nutrition of the Cuban people. Using a ethno-ecological perspective, we identify how people classifyand name the different meats, according to their properties, uses and manners of preparation. The case study considers how the changes in the production patterns of Cuban economy in recent decades have impacted the quantities consumed daily of the different products.